The influence of e-learning and in house training on employee performance with evaluation of kirkpatrick training model as a moderation variable - Taufik Kurrohman; Kabul Wahyu Utomo; Joko Rizkie Widokarti (Enrichment : Journal of Management, 2023)
A Human Resource Management (HRM) is a branch of science in dealing with various challenges within the scope of the organization itself, namely humans. One of the roles of Human Resources Management is to ensure that every employee within the organization has the same vision as the organization so that the organization grows and develops in accordance with the stated goals. This is to ensure that employees have sufficient competence to face challenges, both internal and external to the organization and this is the main key for the organization to grow and survive. One type of employee development in Human Resources Management is through training. One of the training methods that is currently frequently used is e-learning and in-house training. Whether e-learning and in-house training has an impact on performance can be determined by conducting an evaluation. One type of training evaluation is the Kirkpatrick evaluation. Based on the results of this evaluation, it can be concluded from this research that e-learning method training has no effect on employee performance at KPP Madya Karawang and while in-house training method training has an effect on employee performance at KPP Madya Karawang. The hypothesis that the evaluation of Kirkpatrick model training as a moderating variable strengthens the influence of e-learning training on performance is unacceptable, while the hypothesis that the evaluation of Kirkpatrick model training as a moderating variable strengthens the influence of in-house training on performance is acceptable